X-Ray and Radio Polarimetry of the Neutron Star Low-mass X-Ray Binary 4U 1728–34 - Unnati Kashyap; Thomas J. Maccarone; Thomas D. Russell; Mason Ng; Swati Ravi; Eliot C. Pattie; Herman L. Marshall (The Astrophysical Journal)
We report the first X-ray and radio polarimetric results of the neutron star (NS) low-mass X-raydis binary atoll-source 4U 1728−34 using the Imaging X-ray Polarimetry Explorer (IXPE) and Australia Telescope Compact Array. We discovered that the X-ray source was polarized at PD = 1.9% ± 1.0% with a polarization angle of PA = −41° ± 16°. Simultaneous Neutron Star Interior Composition Explorer observations show that the source was in a relatively hard state, marking it as the first IXPE observation of an NS atoll source in the hard state. We do not detect any significant linear polarization in the radio band, with a 3 σ upper limit of 2% at 5.5 GHz and 1.8% at 9 GHz. Combining the radio data sets provides the deepest upper limits on the radio polarization at <1.5% on the linear and circular polarization (measured at 7.25 GHz). The X-ray polarimetric results suggest a source geometry with a Comptonization component possibly attributed to a boundary layer emission or BL emission reflected off the disk , consistent with the other NS atoll sources.